A comparison of brain trauma profiles between elite men's Rugby Union 15s and Rugby Union 7s game play - Paiement, B. (University of Ottawa, 2020)
Head impact and subsequent brain trauma is a concern in contact sports including rugby. Head collisions present acute and long term injury risks to the brain ranging from non-symptomatic, concussion, and neurodegeneration. Rugby Union 15s and Rugby Union 7s are the two most played codes of the sport and the physical and tactical differences may affect how brain trauma is experienced (Cunniffe, Proctor, Baker, & Davies, 2009; Colin W Fuller, Taylor, & Molloy, 2010; L. J. Suarez-Arrones, J. Nunez, Portillo, & Mendez-Villanueva, 2012). It is important to consider all parameters contributing to acute and long term injury risk in order to appropriately capture brain trauma experienced in a contact/collision sport (Karton & Hoshizaki, 2018). Impact frequency, frequency-magnitude, and interval between impact have all been reported to affect brain trauma. Trauma profiling is a method used to describe brain trauma using the variables relating to brain injury risk. The purpose of this study was to compare head impacts experienced in rugby union 15s and 7s using frequency of impact events, frequency-magnitude of brain deformation, and time interval between impacts. Thirty-six hundred (3600) player minutes of footage were analysed for each code, and all head impacts were categorised. Twenty (20) impact conditions were observed and reconstructed. Head to shoulder, hip and knee events were reconstructed using a pneumatic linear impactor, head to head events were reconstructed using a pendulum system, and head to ground events were reconstructed using a monorail drop rig. Results from both codes were compared using non-parametric Mann-Whitney U tests and demonstrated that Rugby 7s had a higher overall frequency of head impact, a greater number of head impacts causing higher trauma , and a shorter time interval between head impacts. These results suggest that rugby 7s presents a greater risk for sustaining brain trauma. These results will help expand the understanding of conditions leading to injury, and may lead to better interventions, such as equipment or rule changes, to mitigate risk.